2015
DOI: 10.3758/s13420-015-0172-3
|View full text |Cite
|
Sign up to set email alerts
|

The Monty Hall dilemma with pigeons: No, you choose for me

Abstract: In the Monty Hall dilemma, humans are initially given a choice among three alternatives, one of which has a hidden prize. After they have chosen, but before revealing whether they have won the prize, subjects are shown that one of the remaining alternatives does not have the prize, and they are asked whether they want to stay with their original choice or switch to the remaining alternative. Switching results in obtaining the prize two thirds of the time, but even after considerable training, humans fail to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a different computerized MHD, humans, pigeons, and, to some extent, preschool children all showed the same general pattern of switching approximately 70%, although there were substantial individual differences (Mazur & Kahlbaugh, 2012). Zentall, Case, and Collins (2015) offered a further exploration of pigeons' responses to the MHD. When the initial choice was made for them (Forced-Choice Group; mirroring the design used by Stibel et al, 2009), pigeons maintained chance levels of switching throughout the experiments.…”
Section: Comparative Approaches To the Monty Hall Dilemmamentioning
confidence: 99%
See 1 more Smart Citation
“…In a different computerized MHD, humans, pigeons, and, to some extent, preschool children all showed the same general pattern of switching approximately 70%, although there were substantial individual differences (Mazur & Kahlbaugh, 2012). Zentall, Case, and Collins (2015) offered a further exploration of pigeons' responses to the MHD. When the initial choice was made for them (Forced-Choice Group; mirroring the design used by Stibel et al, 2009), pigeons maintained chance levels of switching throughout the experiments.…”
Section: Comparative Approaches To the Monty Hall Dilemmamentioning
confidence: 99%
“…These designs offered animals, including humans, much more experience than the classic one-shot MHD does (hundreds or thousands of trials in each reviewed study). In such a context, the contributions of associative principles is more obvious, as when pigeons' switch responses are guided less by endowment effects and more by rote stimulus preferences (Zentall et al, 2015). Further exploration of the comparative psychology of the MHD promises to contribute still more to our understanding of the potential differences between implicit and explicit learning of the task contingencies.…”
Section: Comparative Approaches To the Monty Hall Dilemmamentioning
confidence: 99%
“…Their results showed that participants switched more frequently when their initial selection was randomly determined than participants who freely selected their initial choice. Zentall et al (2015) used a similar methodology of forced initial choices to examine its effect on pigeons' performance. Unlike humans, pigeons that experienced forced initial selections performed worse overall by switching less frequently than pigeons with free selection.…”
mentioning
confidence: 99%